The use of craniofacial superimposition for disaster victim identification. - Wilkinson, Caroline; Lofthouse, Amy (Forensic Science International, 2015)
Skull-to-face comparison is utilised for human identification where there is a suspected identity and the usual methods of identification, such as DNA or dental comparison, are not possible or practical. This research aimed to compare the reliability of manual and computerised craniofacial superimposition techniques and to establish the application of these techniques for disaster victim identification, where there may be a large database of passport-style images, such as the MPUB Interpol database. Twenty skulls (10 females; 10 males) were utilised from the William Bass Skeletal Collection at the University of Tennessee and compared to face pools of 20 face photographs of similar sex, age and ethnic group. A traditional manual photographic method and a new 3D computer-based method were used. The results suggested that profile and three-quarter views of the ante-mortem face were the most valuable for craniofacial superimposition. However, the poor identification rate achieved using images in frontal view suggests that the MPUB Interpol database would not be optimal for disaster victim identification, and passport-style images do not provide enough distinguishing facial detail. This suggests that multiple ante-mortem images with a variety of facial expression should be utilised for identification purposes. There was no significant difference in success between the manual and computer methods.